SOUTH ASIAN RESPONSE TO THE WAR ON TERROR - DR. MOONIS AHMAR (Journal of Political Studies, 2007)
Five years after the U.S. led war on terror, it is time to analyze the response of South Asian countries to the efforts of international coalition to deal with the menace of terrorism. Since September 11, 2001 when terrorism per se got substantial recognition amidst the U.S. led drive against Al-Qaeda, the issue of terrorism in South Asia was viewed differently. Although, almost all the countries of South Asia had suffered enormously from the lethal implications of terrorism prior to the events of September 11, 2001, it was primarily Indo-Pak divergent perceptions on terrorism, which indicated different strategies pursued by New Delhi and Islamabad to deal with the issue of terrorism. While terrorism in South Asia has a political, economic and religious dimensions and causes, it was primarily seen in two perspectives: first, American led war on terror particularly against the non-state actors like Al-Qaeda resulting into its attack on Afghanistan and Iraq. Second, the intensification of Indo-Pak cold war following the terrorist attacks over the Indian parliament on December 13, 2001 and the vicious cycle of charges and counter-charges of cross-border terrorism and state terrorism by both sides against each other. Other South Asian countries, like Bangladesh, Nepal and Sri Lanka also faced the menace of terrorism either in the form of ethnic turmoil, political or religious schism. A major implication of war on terror in South Asia has been severe curbs on various ethnic and religious movements who were believed to have links with foreign terrorist organizations. Therefore, the Tamil tigers and various splinter Tamil groups in Sri Lanka, the Maoist movement in Nepal, the Kashmiri freedom movements in the Indian controlled parts of Jammu and Kashmir and various extremist religious parties and groups in Bangladesh and in Pakistan were perceived to have links with a network of international terrorism and in cases were dubbed as terrorists by the governments of these countries. As far as the response of South Asian countries on the U.S. led war on terror is concerned, four things should be taken into account. First, the diversified nature of response because of bilateral conflicts, particularly between India and Pakistan. Second, the non-implementation of SAARC convention on terrorism by the member countries. Third, the desperation of South Asian countries to get American/Western patronage on the issue of terrorism for monetary purposes. That instead of taking practical steps to eradicate causes which cause terrorism, in most cases, the South Asian regimes wanted to oblige the United States and its highly controversial war on terror. Fourth, using the threat of terrorism as a pretext to curb fundamental freedom and human rights of their citizens also proved a superficial and impractical response of South Asian states for dealing with the issue of terrorism.